Response after treatment with pembrolizumab in a patient with myelophthisis due to melanoma: the role of checkpoint inhibition in the bone. Issue 1 (18th April 2017) - Rosner, Samuel; Sen, Filiz; Postow, Michael
Abstract : Background: Myelophthisis due to melanoma is a rare phenomenon. Treatment strategies for patients with this serious complication of malignancy have not been well documented, and none have previously reported efficacy of immune checkpoint inhibition. Since bone metastases are not measurable lesions per standard response criteria, the efficacy of immune checkpoint inhibition in the bones is also not well described. Case presentation: We describe a patient with widespread melanoma metastases involving the bone marrow causing myelophthisis and pancytopenia who responded to immune checkpoint inhibition with the anti-programmed cell death-1 (PD-1) inhibitor pembrolizumab. Conclusions: This is the first report to our knowledge of disease response to immune checkpoint inhibition in a patient with myelophthisis. Clinical trials have recently emerged describing the efficacy of PD-1 inhibition for disorders regularly involving the bone marrow, such as hematologic malignancies, suggesting the importance of better understanding the bone marrow as an immunologically active compartment. Clinicians should be aware that immune checkpoint inhibition alone may be effective in treating malignancy involving the bone marrow, even in cases of extensive involvement resulting in pancytopenia due to myelophthisis from a solid tumor as our case suggests.